(untitled) (Antologia di Diritto Pubblico, 2023)
The editorial, authored by Prof. Anna Maria Poggi, anticipates the subject of the next issue of the Journal. In particular, it aims to illustrate the current relevance of the reflection carried out by Gaspare Ambrosini (1886-1985) in his well-known 1933 essay on the regional state.